Implementing Learning Strategies for Moderate Islamic Religious Education in Islamic Higher Education - Muhammad Anas Ma`arif; Muhammad Husnur Rofiq; Akhmad Sirojuddin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
Religious Moderation in education is important to implement because it can bring a deterrent effect to the students’ religious understanding and practice to avoid radicalism in higher education. The present study is aimed at investigating learning strategies to deliver Islamic Religious Education in higher education. A qualitative method with a case study approach was applied in this study. The data were collected by using interview, documentation, and observation. The results show that the university applied several learning strategies to strengthen students’ psychomotor and affective aspects in the form of experiential, habituation, emotional, functional, and rational strategies. Those strategies can be implemented by using various learning methods such as lectures, discussions, experiments, and assignments that promote moderate Islamic values and Rahmatan LiAlaminin.